Studi Komunikasi Lingkungan Melalui Komunikasi Kelompok Terhadap Edukasi Pengelolaan Lingkungan Dengan Pendekatan Teori Strukturasi Adaptif Pada Masyarakat Kota Malang - Pravinska Aldino, Reza Safitri, Antoni (Linimasa : Jurnal Ilmu Komunikasi, 2020)
Environmental management education is a strategy or concept that can be understood by the community personally to protect the environment, take precautions, improve the quality of the environment and be careful of threats to human health and the environment. The Recapitulation of the Malang City Control and Operations Center (Pusdalops PB) in 2019 noted that Bareng and Bandungrejosari sub-districts were included in densely populated areas, thereby reducing the capacity of absorptive capacity which resulted in land movement and increased flooding during the rainy season. The problem studied is how the group decision process carried out by the people of Kelurahan Bandungrejosari and Kelurahan Bareng through kelurahan tangguh as a forum for environmental management education. Cox (2010) sees environmental communication as a more holistic view of pragmatic and constitutive ways to understand the environment and human relations with the natural world. The establishment of resilient kelurahan can also be called group communication which is a gathering place for members to achieve common goals and decision making. The aim is to care for the environment and recognize the potential for disasters in the residential areas of the community (Kelurahan Bandungrejosari and Kelurahan Bareng) to ensure a sustainable life. In kelurahan tangguh each group member can interact with each other both face to face and using certain media / communication tools. In addition there are patterns among group members and continue to grow unnoticed, these patterns are generated through a set of rules and resources owned by group members (Gouran, 2016). Marshall Scott Poole in adaptive structuration theory explains that group decision making is a process in which group members try to create unity and final decisions so as to reach consensus. Poole divides into three dimensions, namely interpretation, morality and strength.